IDENTIFICATION OF AIR RADAR TARGETS USING THE DOPPLER EFFECT FROM A HEATED JET ENGINE - P. Sh. Adalaeva; T. G. Aigumov; S. V. Magomedova; T. A. Chelushkina (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Objectives The aim of the study is to develop a methodology for identifyingaircraft by the deflections of an electromagnetic radar beam by a heated jet engine. Methods Atoms of the crystal lattice of the metallic parts of the operating jet engine will be in a state of chaotic Brownian motion due to heating. The electromagnetic beam, falling on these atoms, will change its frequency in accordance with the Doppler effect, by means of which the spectral electromagnetic radiation component will expand in direct proportion to the magnitude of the engine temperature. When determining the width of the spectral line of the direction-finding radio emission, it is possible to accurately identify the temperature of the aircraft in order to avoid false targets.Results When locating aircraft having a working jet engine, it is possible not only to determine the coordinates of the target, but also to identify the heated engine. Due to the use of high-precision methods for identifying heated sections, the direction-finding targets may be classified, the spatial orientation of both the aircraft itself and its control planes to be determinedand the direction of the thrust vector control of the jet engine calculated.Conclusion The application of an innovative technique for direction-finding air targets will allow the radar targets to be identified with high accuracy against the background of active and passive interferences. In addition, when analysing the information on the magnitude and direction of the jet engine thrust and the position of the aircraft controls, it is possible to determine not only the coordinates of the direction-finding object, but also to proactively identify the manoeuvres to be performed.